Cyber-Victimization and Cyberbullying: The Moderator Effects of Emotion Regulation from Perpetrators - Costly Ifada; Sunawan Sunawan (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Cyberbullying is a form of behavior that harms, disrupts, and threatens the safety of other users on social media. Cyberbullying is crucial to explore, considering that most research focuses on victims and less on perpetrators. The present study aimed to examine the role of emotion regulation in moderating cyber-victimization and cyberbullying. This correlational study involved 103 respondents (38 males and 65 females). They are aged 19-24, in the second to fourteenth semesters, and indicated as a perpetrator of social media. Data were collected using the Emotion Regulation Questionnaire (ERQ) and the Cyberbullying Inventory (CB-I). The data analysis techniques applied in this study were descriptive, correlational, cluster, and regression-based moderator analyses. The moderator analysis used the PROCESS syntax in IBM SPSS. This study showed that emotion regulation predicted decreasing cyberbullying, whereas cyber-victimization strongly correlated with cyberbullying. Furthermore, the negative correlation between cyber-victimization and cyberbullying increased when emotion regulation was low. This study confirmed that most perpetrators experienced cyber-victimization, and emotion regulation strategically reduced those circumstances.